Associations between Physical Activity with Health-Related Quality of Life and Wellbeing among Children with and without Autism - Okan Sari, Hanife Banu, Ataman Yanci, Halil Bişgin, Mahmut Öztürk (Pakistan Journal of Medical & Health Sciences, 2022)
ABSTRACT Purpose: Evidence revealed that physical activity has positive effects on quality of life and mental health. Nevertheless, this topic has received little attention among special groups such as autism. Thus, this study was designed to examine the associations between physical activity with health-related quality of life and wellbeing among children with autism. Method: 65 children with autism (aged 9 to 13 years old) from special school and 70 typically developing children from regular primary schools (aged 9 to 12 years old) participated in this study. Physical activity, health-related quality of life, and wellbeing were measured by using standard questionnaires. Pearson correlation, regression analysis, and independent t test were used for data analysis. Results: Both children with and without autism had low physical activity. Children without autism had significantly higher levels of physical activity, health-related quality of life, and wellbeing compared with children with autism. Physical activity was positively associated with health-related quality of life and wellbeing among both children with and without autism. Conclusion: These findings, together, indicate that physical activity is a critical concern for children with autism. Accordingly, it is necessary to adopt appropriate strategies to increase the level of physical activity among children with autism.